The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/aem.07593-11
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence for Transmission of Antibiotic-Resistant Escherichia coli Strains from Humans to Wild Western Lowland Gorillas in Lopé National Park, Gabon

Abstract: ABSTRACTThe intensification of human activities within the habitats of wild animals is increasing the risk of interspecies disease transmission. This risk is particularly important for great apes, given their close phylogenetic relationship with humans. Areas of high human density or intense research and ecotourism activities expose apes to a high risk of disease spillover from humans. Is this risk lower in areas of low human density? We determined the prevalence of Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
(44 reference statements)
3
38
1
Order By: Relevance
“…Resistance against β -lactum was followed by resistance to aminoglycosides such as strA and strU and then by resistance to tetracyclines such as tetA and tetD. A similar tendency was observed in Lopé National Park, where the prevalence of antibioticresistant E. coli was studied in wild gorillas and villagers living adjacent to the national park (Benavides et al 2012). These authors reported that the most prevalent resistance in E.coli from both gorillas and humans was ampicillin resistance, followed by streptomycin resistance and tetracycline resistance.…”
Section: Antibiotic Resistancesupporting
confidence: 55%
See 1 more Smart Citation
“…Resistance against β -lactum was followed by resistance to aminoglycosides such as strA and strU and then by resistance to tetracyclines such as tetA and tetD. A similar tendency was observed in Lopé National Park, where the prevalence of antibioticresistant E. coli was studied in wild gorillas and villagers living adjacent to the national park (Benavides et al 2012). These authors reported that the most prevalent resistance in E.coli from both gorillas and humans was ampicillin resistance, followed by streptomycin resistance and tetracycline resistance.…”
Section: Antibiotic Resistancesupporting
confidence: 55%
“…However, these techniques were developed in Bossou, Guinea, where a manipulation room was available within the field. Recent study in Lopé National Park, Gabon, also showed successful cultivation of Escherichia coli from wild animals such as gorillas (Benavides et al 2012). Such study was based on the laboratory facility on site.…”
Section: Introductionmentioning
confidence: 99%
“…This study is one of few to examine antimicrobial resistance in a broad range of hosts (both in absolute numbers and breadth of species) in their natural environment (Gordon and Cowling 2003;Benavides et al 2012;Lescat et al 2013) and the first to use a comparative lifehistory study design to evaluate potential mechanisms of exposure across different land-use areas.…”
Section: Discussionmentioning
confidence: 99%
“…The development of antimicrobial resistance is a complex phenomenon, arising by direct selection from clinical or agricultural antibiotic use, independent selection by naturally occurring heavy metals and antibiotics, or via the transfer of naturally occurring resistance elements from environmental bacteria (Allen et al 2010;Wellington et al 2013). The presence of antimicrobial resistance in wildlife also does not necessarily imply direct transmission from humans (Benavides et al 2012), and horizontal gene movement readily occurs in areas of high microbial density (Salyers et al 2004;Schlü ter et al 2007), allowing resistance determinants to be exchanged between microorganisms. Molecular evaluations, such as repetitiveelement PCR (Goldberg et al 2006), will be essential to determine the dynamics of transmission in this system, and are underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli diversity and population dynamics have been the focus of recent studies (17)(18)(19)(20) investigating the relationship between E. coli populations and proxies of interhost contacts. For example, E. coli sharing between human, primates, and livestock increased with the frequency and intensity of interspecies contacts in Uganda (21).…”
mentioning
confidence: 99%